Analysis of Hajj Management Policy in Indonesia - Nursahidin; Suryadi; Mohammad Taufik Hidayat; Raden Mahendra Haryo Bharoto (Journal Socio Humanities Review, 2025)
The Hajj pilgrimage is one of the Five Pillars of Islam, obligatory for every Muslim who is physically and financially capable. As the country with the largest Muslim population in the world, Indonesia faces significant challenges in managing the Hajj pilgrimage for its citizens. This study analyzes the Hajj management policies in Indonesia, focusing on the differences between Regular Hajj, ONH Plus, and Puroda Hajj, as well as the impact of Hajj loan schemes and the illegal practices of selling Hajj packages by travel agencies. The results indicate that the policies implemented by the Indonesian government still face various challenges, including long waiting lists for Regular Hajj, high costs for ONH Plus and Puroda Hajj, and risks associated with the sale of Hajj packages using non-Hajj visas. This study provides recommendations for policy improvements, including revising the queue system, stricter enforcement against illegal practices, and exploring alternative financing options that do not impose long-term financial burdens on pilgrims. It is hoped that these findings can contribute to the development of more effective policies in managing the Hajj pilgrimage in Indonesia.